Brain Gray Matter Deficits at 33-Year Follow-Up in Adults with Attention-Deficit/Hyperactivity Disorder Established in Childhood - Proal, Erika (2011)
CONTEXT: Volumetric studies have reported relatively decreased cortical thickness and gray matter volumes in adults with Attention-Deficit/Hyperactivity Disorder (ADHD) whose childhood status was retrospectively recalled. We present the first prospective study combining cortical thickness and voxel-based morphometry (VBM) in adults diagnosed with ADHD in childhood. OBJECTIVE: In adults who had Combined Type ADHD in childhood, to 1) test whether they exhibit cortical thinning and decreased gray matter in regions hypothesized related to ADHD, and 2) test whether anatomic differences are associated with current ADHD diagnosis, including persistence versus remission. DESIGN: Cross-sectional analysis embedded in a 33-year prospective follow-up at mean age 41. SETTING: Research outpatient center. PARTICIPANTS: ADHD probands were from a cohort of 207 6–12 year old Caucasian boys; male comparison subjects (n=178) had been free of ADHD in childhood. We obtained MRI scans in 59 probands and 80 comparisons (28% and 45% of original samples, respectively). MAIN OUTCOME MEASURE: Whole-brain VBM and vertex-wise cortical thickness analyses. RESULTS: Cortex was significantly thinner in ADHD probands than comparisons in the dorsal attentional network and limbic areas (FDR<0.05, corrected). Additionally, gray matter was significantly decreased in probands in right caudate, right thalamus and bilateral cerebellar hemispheres. Probands with persistent ADHD (n=17) did not differ significantly from remitters (n=26) at FDR<0.05. At uncorrected p<0.05, remitters had thicker cortex relative to those with persistent ADHD in medial occipital cortex, insula, parahippocampus, and prefrontal regions. CONCLUSIONS: We observed anatomic gray matter reductions in adults with childhood ADHD, regardless of current diagnosis. The most affected regions underpin top-down control of attention and regulation of emotion and motivation. Exploratory analyses suggest that diagnostic remission may result from compensatory maturation of prefrontal, cerebellar, and thalamic circuitry.